Meta-analysis identifies seven susceptibility loci involved in the atopic march - Marenholz, Ingo; Esparza-Gordillo, Jorge; Rüschendorf, Franz; Bauerfeind, Anja; Strachan, David P.; Spycher, Ben D.; Baurecht, Hansjörg; Margaritte-Jeannin, Patricia; Sääf, Annika; Kerkhof, Marjan; Ege, Markus; Baltic, Svetlana; et al. (Nature communications, 2015)
Eczema often precedes the development of asthma in a disease course called the ‘atopic march’. To unravel the genes underlying this characteristic pattern of allergic disease, we conduct a multi-stage genome-wide association study on infantile eczema followed by childhood asthma in 12 populations including 2,428 cases and 17,034 controls. Here we report two novel loci specific for the combined eczema plus asthma phenotype, which are associated with allergic disease for the first time; rs9357733 located in EFHC1 on chromosome 6p12.3 (OR 1.27; P= 2.1 × 10 −8 ) and rs993226 between TMTC2 and SLC6A15 on chromosome 12q21.3 (OR 1.58; P= 5.3 × 10 −9 ). Additional susceptibility loci identified at genome-wide significance are FLG (1q21.3), IL4/KIF3A (5q31.1), AP5B1/OVOL1 (11q13.1), C11orf30/LRRC32 (11q13.5) and IKZF3 (17q21). We show that predominantly eczema loci increase the risk for the atopic march. Our findings suggest that eczema may play an important role in the development of asthma after eczema. The development of asthma following eczema is known as the atopic march. Here the authors conduct a GWAS on affected children and identify two novel loci associated with the disease phenotype.